Analisis Hubungan Pengetahuan Tentang Limbah B3 dengan Praktik Penanganan Sampah Elektronik Pada Mahasiswa FKM UHO - Muhammad Anugrah Bawia; Siti Rabbani Karimuna; Nurosa Sabila; Halma Halma; Dewi Sartika; Fairul Kader (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Electronic waste (e-waste) management has become an increasingly important environmental and public health issue among university students. This study aimed to analyze the relationship between knowledge of hazardous and toxic waste (B3 waste) and electronic waste handling practices among students of the Faculty of Public Health, Universitas Halu Oleo. This study used a quantitative design with an analytical approach. A total of 40 respondents were selected using a purposive sampling technique. Data were collected through questionnaires to measure the level of knowledge and e-waste handling practices, then analyzed using Fisher’s Exact Test with a significance level of α = 0.05.he results showed that 21 respondents (52.5%) had good knowledge, while 30 respondents (75.0%) still demonstrated poor e-waste handling practices. Among respondents with poor knowledge, 18 individuals (94.7%) had poor handling practices, whereas among those with good knowledge, 12 individuals (57.1%) still showed poor handling practices. Statistical analysis indicated a significant relationship between knowledge of hazardous and toxic waste and e-waste handling practices (p = 0.009). his study concludes that knowledge is associated with electronic waste handling practices among university students. It is recommended that the university provide e-waste drop boxes, conduct regular educational programs regarding electronic waste management, and collaborate with licensed hazardous waste management agencies to support safe and sustainable e-waste management.